2020
DOI: 10.3390/nu12072115
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Supplementation of Food Ingredient (Prebiotic) or Food Contaminant (Mycotoxin) Influences Mucosal Immune System in Piglets

Abstract: The early life period is crucial for the maturation of the intestinal barrier, its immune system, and a life-long beneficial host–microbiota interaction. The study aims to assess the impact of a beneficial dietary (short-chain fructooligosaccharides, scFOS) supplementation vs. a detrimental dietary environment (such as mycotoxin deoxynivalenol, DON) on offspring intestinal immune system developmental profiles. Sows were given scFOS-supplemented or DON-contaminated diets during the last 4 weeks of gestation, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In addition, prebiotics could enhance immune responses and modulate the responses to pathogens or toxins. [35][36][37][38] Oligosaccharides are prebiotics reported to significantly enhance the growth of probiotic bacteria, such as Bifidobacteria and Lactobacilli. In addition, oligosaccharides may reduce pathogen adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prebiotics could enhance immune responses and modulate the responses to pathogens or toxins. [35][36][37][38] Oligosaccharides are prebiotics reported to significantly enhance the growth of probiotic bacteria, such as Bifidobacteria and Lactobacilli. In addition, oligosaccharides may reduce pathogen adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The concerns about weaning stress and its concurrent symptoms have always aroused great caution in the animal industry. Previous work demonstrated that the gut microbiota of mammals has a large number of roles benefiting the host–such as digestion and fermentation of carbohydrates [ 3 ], production of vitamins [ 4 ], maintenance of normal functions of the intestinal villi [ 5 ], regulation of the immune responses [ 6 ], and protection from pathogenic bacteria [ 7 ]. However, the gut microbiota of piglets is a complex ecosystem showing dynamic composition and diversity, which could change with age and diet [ 8 ].…”
Section: Introductionmentioning
confidence: 99%